Stand-alone and combined effects of protein hydrolysate and humic-like substances derived from waste materials on the growth, physiology and mineral nutrition of tea nursery plants - Raguraj, Sriharan; Kasim, Susilawati; Sanali, Bellana Vithanage Roshika; Senarathne, Thakshala Thilini Kumari; Weerathunga, Saman Kumara; Damayanthi, Maha Makkalage Nalika; Wijesinghe, Senarath Pathiranalage Shyamali Kumari; Amali, Rathnasekara Kuruppu Arachchige; Madushani, Maha Gamage Kusala; Liyanage, Liyana Rallage Mahesh Chaminda (Springer, 2024)
This study was designed to investigate the effects of individual and combined application of protein hydrolysate (PH) and humic-like substances (HLS) along with the reduction of fertilizer on the growth, physiological and biochemical parameters and mineral nutrition of tea nursery plants. Individual and combined effects of biostimulants were evaluated in a randomized complete block factorial experimental design with three replications. The experiment consisted of three levels of fertilizer (100%, 75% and 50%) and four biostimulant treatments (Control, PH, HLS and PH + HLS). Combined (PH + HLS) and individual application of biostimulants increased the leaf count and number of active buds by 44.8% and 52.3% respectively, compared to untreated plants. PH and combined treatments produced significantly higher and comparable total plant biomass under 75% and 100% fertilizer levels compared to control + 100% fertilizer. Positive effect exerted by HLS alone on total plant biomass was comparatively lower than PH and PH + HLS while significantly higher than control. PH application significantly increased the net photosynthetic rate (+ 30%), stomatal conductance (+ 48%) and concentration of CO2 in intracellular space (+ 36%) compared to control plants. All the biostimulant treatments positively affect the chlorophyll, total soluble sugars and proline contents in tea leaves, where higher values were recorded in PH treatment. Leaf N concentration was significantly increased by individual application of PH and HLS, while leaf P concentration was enhanced by PH and combined treatments. Leaf K, Mg and Ca concentrations were not influenced by biostimulant treatments. PH and combined treatments produced higher and similar effects on the growth of tea nursery plants with 75% and 100% fertilizer levels while HLS alone showed comparatively lower positive effects. It can be concluded that foliar application of PH alone or combining PH with HLS enhanced the growth performance of tea nursery plants along with a saving of chemical fertilizer by 25%.